Parkinson's disease and transplants - Barker, Roger (Henry Stewart Talks, 2007)
Pathological features of Parkinson's disease, Limitations of current drug therapies, Possible alternative therapies, Deep brain stimulation, Growth factor infusions, Neural transplants, Human fetal allograph transplants, Issues facing neural grafting in PD, Implications for cell therapies for all neurological disorders
Updated at 2020/12/02